2008
DOI: 10.1038/onc.2008.183
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2-ERG fusion, a common genomic alteration in prostate cancer activates C-MYC and abrogates prostate epithelial differentiation

Abstract: The high prevalence of TMPRSS2-ERG rearrangements (B60%) in prostate cancer (CaP) leads to androgenic induction of the ETS-related gene (ERG ) expression. However, the biological functions of ERG overexpression in CaP remain to be understood. ERG knockdown in TMPRSS2-ERG expressing CaP cells induced striking morphological changes and inhibited cell growth both in cell culture and SCID mice. Evaluation of the transcriptome and specific gene promoters in ERG siRNA-treated cells and investigation of gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
250
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(272 citation statements)
references
References 22 publications
18
250
1
Order By: Relevance
“…7,19 Our laboratory has recently reported that TMPRSS2-ERG fusion, a common genomic alteration in CaP, activates C-MYC and abrogates prostate epithelial differentiation, suggesting a potential mechanism for the early C-MYC overexpression in a significant subset of CaP. 24 Indeed, in a cohort of well/moderately differentiated prostate tumors, in which other confounding genomic alterations may be minimal, we did find a highly significant correlation of ERG and C-MYC expression. 24 In this study, we further assessed whether C-MYC mRNA overexpression in primary prostate tumors was predictive of more aggressive tumor or disease progression.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…7,19 Our laboratory has recently reported that TMPRSS2-ERG fusion, a common genomic alteration in CaP, activates C-MYC and abrogates prostate epithelial differentiation, suggesting a potential mechanism for the early C-MYC overexpression in a significant subset of CaP. 24 Indeed, in a cohort of well/moderately differentiated prostate tumors, in which other confounding genomic alterations may be minimal, we did find a highly significant correlation of ERG and C-MYC expression. 24 In this study, we further assessed whether C-MYC mRNA overexpression in primary prostate tumors was predictive of more aggressive tumor or disease progression.…”
Section: Discussionmentioning
confidence: 56%
“…24 Indeed, in a cohort of well/moderately differentiated prostate tumors, in which other confounding genomic alterations may be minimal, we did find a highly significant correlation of ERG and C-MYC expression. 24 In this study, we further assessed whether C-MYC mRNA overexpression in primary prostate tumors was predictive of more aggressive tumor or disease progression. Our approach was to quantitatively determine C-MYC mRNA expression levels in micro-dissected tumor cells and matched benign epithelial cells in a radical prostatectomy cohort with long follow-up data available.…”
Section: Discussionmentioning
confidence: 57%
“…Although TMPRSS2 -ERG fusion has typically been reported as prevalent in 40 -50% of prostate tumours, the range has varied by as much as 25 -60% (Nam et al, 2007;Setlur et al, 2008;Sun et al, 2008;Yoshimoto et al, 2008;Hofer et al, 2009;Mosquera et al, 2009). The techniques used for TMPRSS2 -ERG detection, novel potential fusion products and genetic differences in population cohorts may account for these discrepancies.…”
mentioning
confidence: 80%
“…Consensus ERG binding site mutations corresponding to nt À121 to À114 (5 0 -GGAGGAAG-3 0 to 5 0 -GGTAAAAG-3 0 ) and to nt À112 to À106 (5 0 -GTAG-GAG-3 0 to 5 0 -GTCGGAG-3 0 ) were constructed using the OPN-136/þ77 luciferase wild-type fragment as the template. Oligonucleotides encoding for small hairpin RNAs (shRNA) against ERG mRNA [targeted sequence described in (32)] was synthesized with appropriate loop and cohesive ends sequences according to the plasmid provider instructions and was cloned into pSilencer 2.1-U6 (Ambion Inc). All constructs were verified by sequencing (Genoscreen) and restriction enzyme digestion.…”
Section: Plasmid Constructsmentioning
confidence: 99%